Synthesis, structures, thermal behavior and vapour pressures of new strontium and barium β-diketonate complexes [M(t-BuCOCHCOCF3)2(18-crown-6)] and [M(t-BuCOCHCOC3F7)2(18-crown-6)] (M = Sr, Ba). (1st February 2020) - Pochekutova, Tatiana S.; Khamylov, Vyacheslav K.; Fukin, Georgy K.; Petrov, Boris I.; Shavyrin, Andrey S.; Arapova, Alla V.; Lazarev, Nikolay M.; Faerman, Vladimir I.; Kulikova, Tatiana I.; Baranov, Evgeny V.; Khamaletdinova, Nadia M.
Graphical abstract: The synthesis, characterization, structural studies and thermal investigations of the new complexes [Sr(fod)2 (18-crown-6)], [Ba(fod)2 (18-crown-6)] (fod = 1, 1, 1, 2, 2, 3, 3-heptafluoro-7, 7-dimethyloctane-4, 6-dionato), [Sr(pta)2 (18-crown-6)] and [Ba(pta)2 (18-crown-6)] (pta = 1, 1, 1-trifluoro-5, 5-dimethylhexane-2, 4-dionato) were performed. Highlights: Synthesis, X-ray structure analysis and physical properties of the new Strontium and Barium β-diketonate complexes [Sr(pta)2 (18-crown-6)], [Ba(pta)2 (18-crown-6)], [Sr(fod)2 (18-crown-6)], [Ba(fod)2 (18-crown-6)]. The chemical bond nature, the charges distribution, and the intermolecular interactions energy for [Ba(fod)2 (18-crown-6)] using an approach based on molecular invariom. Abstract: The monomeric β-diketonate complexes with 18-crown-6 [Sr(pta)2 (18C6)] (1 ), [Sr(fod)2 (18C6)] (2 ) [Ba(fod)2 (18C6)] (3 ), [Ba(pta)2 (18C6)] (4 ) [pta = 1, 1, 1-trifluoro-5, 5-dimethylhexane-2, 4-dionato; fod = 1, 1, 1, 2, 2, 3, 3-heptafluoro-7, 7-dimethyloctane-4, 6-dionato; 18C6 = 18-crown-6 (18-crown-6 = 1, 4, 7, 10, 13, 16 – hexaoxacyclooctadecane)] were synthesized by the reactions of alkaline-earth metal with 2 eq. of corresponding β-diketone and 1 eq. of 18-crown-6 in ethanol. The solvated complex [Ba(pta)2 (18-crown-6)](CH2 Cl2 ) (5 ) was obtained by recrystallisation of 4 from CH2 Cl2 - pentane solution. Complexes 1 –4 were characterized by elemental analysis, IR-, 1 H, 19 F, 13 C NMR-spectroscopy and mass-spectrometry. The crystal structures of complexes 1 –3 and 5 were investigated by X-ray diffraction analysis. The melting and decomposition ranges of 1 –4 have been determined by differential scanning calorimetry. The saturated vapor pressures were measured by Khudsen effusion method in temperature ranges 389–419, 407–435, 394–429, 434–478 K for 1, 2, 3 and 4 respectively, the enthalpies and the entropies of their sublimation are determined. The chemical bond nature, the charges distribution, and the intermolecular interactions energy were investigated in 3 using an approach based on the molecular invariom.